Building Collective Identity: A Pragmatic Analysis of Deixis Persona in Indonesian Political Discourse - Khofifah Indah Baitul Jannah; Silvia Al Viana (Universitas Negeri Semarang, 2026)
This research examines the pragmatic function of persona deixis in Indonesian political discourse, focusing specifically on President Prabowo Subianto's inaugural speech at the MPR Plenary Session on October 20, 2024. Previous studies on persona deixis in political speeches have largely focused on classifying deixis types without thoroughly analyzing their ideological and identity-constructing functions. This study addresses that gap by analyzing how pronoun choices construct collective identity in a post-electoral context. Using a descriptive qualitative method that combines pragmatic analysis with a critical discourse analysis (CDA) perspective, data were collected through documentation and close reading of the official speech text published by the State Secretariat of the Republic of Indonesia. Analysis was conducted through data reduction, classification of persona deixis forms (saya, kami, kita, mereka), contextual analysis, and social function interpretation. The results showed that (1) saya functions to establish personal authority and responsibility, (2) kami constructs institutional legitimacy, (3) kita builds inclusive national solidarity and collective identity; and (4) mereka marks political boundaries while simultaneously enabling reconciliation. These findings demonstrate that persona deixis operates as a multi-layered discursive strategy for legitimation, solidarity-building, and in-group/out-group management. This study contributes theoretically to pragmatic and CDA scholarship by offering an integrated analytical framework for persona deixis as an ideological instrument in political speech, and practically by advancing critical literacy toward Indonesian political language.